Immunomodulatory Properties of Mesenchymal Stromal Cells: An Update - Müller, Luise; Tunger, Antje; Wobus, Manja; von Bonin, Malte; Towers, Russell; Bornhäuser, Martin; Dazzi, Francesco; Wehner, Rebekka; Schmitz, Marc (Frontiers in Cell and Developmental Biology, 2021)
Mesenchymal stromal cells (MSCs) are characterized by an extraordinary capacity to modulate the phenotype and functional properties of various immune cells that play an essential role in the pathogenesis of inflammatory disorders. Thus, MSCs efficiently impair the phagocytic and antigen presenting capacity of monocytes/macrophages and promote the expression of immunosuppressive molecules such as interleukin (IL)-10 and programmed cell death 1 ligand 1 by these cells. They also effectively inhibit the maturation of dendritic cells and their ability to produce proinflammatory cytokines and to stimulate potent T-cell responses. Furthermore, MSCs inhibit the generation and proinflammatory properties of CD4+ T helper (Th)1 and Th17 cells, while they promote the proliferation of regulatory T cells and their inhibitory capabilities. MSCs also impair the expansion, cytokine secretion, and cytotoxic activity of proinflammatory CD8+ T cells. Moreover, MSCs inhibit the differentiation, proliferation, and antibody-secretion of B cells, and foster the generation of IL-10-producing regulatory B cells. Various cell membrane-associated and soluble molecules essentially contribute to these MSC-mediated effects on important cellular components of innate and adaptive immunity. Due to their immunosuppressive properties MSCs emerged as promising tools for the treatment of inflammatory disorders such as acute graft-versus-host disease, graft rejection in patients undergoing organ/cell transplantation, and autoimmune diseases.